(untitled) (Research, Society and Development, 2021)
Objective: to map in the literature the recommendations and considerations on the use of integrative and complementary practices in patients with COVID-19, identifying the perspectives and gaps that exist in this production. Method: a scoping review, carried out in the following databases: National Library of Medicine via PubMed®, Current Nursing and Allied Health Literature, Scopus, Embase, Web of Science, Latin American and Caribbean Literature on Health Sciences via the National Health Library, Americas Traditional Complementary and Integrative Medicine and in the National Observatory of Traditional, Integrative and Complementary Knowledge and Practices, including 20 studies with different methodological approaches that answered the following question: “What are the recommendations or considerations on the use of integrative and complementary practices in patients with COVID-19?” Results: the studies were originated mainly in China, presented varied methodological designs, and addressed 13 of the 29 practices included in the National Policy of Integrative and Complementary Practices. Among these, Traditional Chinese Medicine, with discussions involving phytotherapy, stood out. In general, the practices acted mainly in reducing the symptoms caused by COVID-19 and can contribute to the treatment of the disease. Conclusion: although there is an urgent need for more studies that investigate the use of integrative and complementary practices in patients with COVID-19, these therapies can assist in the treatment, in the prevention of diseases, and in the recovery of the patients.